ANALISA TRIANGULAR FUZZY NUMBER DALAM PERANCANGAN METODE AHP (ANALYTICAL HIERARCHY PROCESS) - Hariyanto, Krisnadhi (Fakultas Teknik Universitas Wisnuwardhana, 2015)
The study aims to design decision support system using triangular fuzzy number approach in Analytical Hierarchy Process method. The Analytical Hierarchy Process (AHP) is one of the decision support system method which controls experiences and intuition but critical at coupled comparative scales because it uses crisp. A triangular fuzzy number is used to approach AHP scale so as to obtain more fexible value of coupled comparison. The triangular fuzzy number-AHP method uses analysis synthetic extent in the priority processing implemented on ranking cases of potential acceptors of scholarship of PPA and BBM in Wijaya Putra University of Surabaya. The result is the average of mismatch between the result by triangular fuzzy number-AHP method and the result of manual work which are 23.93% of the PPA scholarship and 27,35% of the BBM scholarship.